Analogije med poezijo S. Kosovela in C. Rebore oziroma ali obstaja italijanski ekspresionizem? - Betocchi, Darja (Primerjalna književnost, 2005)
According to contemporary Italian literary criticism, examples of both futurism and expressionism can be found in Italian literature. Segre and Martignoni detect explicit expressionist characteristics of style and theme in the work of the so-called "poeti vociani", who were first published in the Florentine review La voce (1908-1914, 1914-1916). In fact, they go as far as to say that "the best 'vociani' represented the true literary avant-garde of the pre-WWI period (Testi nella storia 4, La letteratura italiana dalle Origini al Novecento, 2001)." Their opinion seems rather tendentious, if not ideologically biased, but one can equally question the somewhat radical thesis of Kralj which claims a total absence of expressionistic texts in Italian literature (Lado Kralj, Ekspresionizem, 1986). A close analysis of the poems and letters of C. Rebora (1885-1957), one of the most eminent "poeti vociani", puts such propositions about the existence of Italian expressionism to the test. Comparing Rebora's opus (up to 1926/27) with the opus of S. Kosovel, I searched for any shared expressionist elements, taking the three major expressionist themes as guideline clusters for my analysis: - an awareness of crisis and a revolt against modern civilizationč - feelings of loneliness, solitude, existential meaninglessness, alienation, inner disharmony, loss of identity, in other words - "dissociation of the subject". - responses to these feelings: either glorifying the poet's prophetic function and praising the soteriological role of poetry, or prophesying the demise of European civilization, and announcing the birth of a new world and new human. Rebora's poetry deals with all these themes, revealing, at times, a striking similarity with certain motifs in the poetry of Srečko Kosovel. Despite the fact that a stylistic analysis also confirms the thesis about Rebora's expressionism, there is insufficient evidence to show that Rebora - along with other "vociani" poets - was familiar with German expressionism. This, on the contrary, cannot be said of Kosovel. The lack of influence of German expressionists on the Italian "vociani" may be explained first by the simultaneous appearance of the "vociani" poets and the German expressionists on the literary scene; and second, by scant know-ledge of contemporary German literature among Italian writers at the time. Any possibility of German literature influencing the "vociani" poets should thus be excluded. To conclude: expressionism as a literary movement proper did not exist in Italy. There were, however, decidedly expressionist elements in the work of certain authors. The surprising analogies observed between German and Slovenian expressionism can, on the other hand, be explained by a general awareness of the cultural-historical crisis of Western civilization of the time.
Keywords: Kosovel, Srečko, 1904-1926; Reboro, Clemente; slovenska poezija; italijanska poezija; ekspresionizem; Expressionism; literarni vplivi